Model of A Critical Size Defect in the New Zealand White Rabbit’s Tibia - Che Seman, Che Nor Zarida; Zakaria, Zamzuri; Sharifudin, Mohd Ariff; Ahmad, Aminudin Che; Awang, Mohd Shukrimi; Mohd Yusof, Nazri; Buyong, Zunariah (IIUM Medical Journal Malaysia, 2018)
Introduction: Critical size defects (CSD) in the long bones of New Zealand White rabbits (Oryctolagus cuniculus) have been used for years as an experimental model for investigation of the effectiveness of a new bone substitute material. There are varieties of protocols available in the literature. This technical note attempts to present an alternative surgical technique of a CSD in the New Zealand white rabbit tibia. Methods: Thirty-nine New Zealand White rabbits were used in this study. A CSD of approximately 4.5 mm (width) X 9.0 mm (length) was surgically drilled at the proximal tibial metaphysis, approximately 1 cm from the knee joint. The surrounding of soft tissue was repositioned and sutured layer by layer with bioabsorbable surgical suture. Two x-rays of anteroposterior and lateral were taken before assessed under computed tomography scan at 6, 12 and 24 weeks. Results: This alternative method created CSD with less bleeding from the muscle observed. No mortality or other surgical complications observed within 6 weeks, 12 weeks and 24 weeks following surgery. Conclusion: A simple and safe method for performing CSD was demonstrated and recommended as an alternative approach for surgery on New Zealand White rabbits.